PENERAPAN LKS EKSPERIMEN BERBASIS KONTEKSTUAL PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN TERHADAP HASIL BELAJAR SISWA KELAS XI SMA NEGERI 4 LEIHITU - Napsin Palisoa; Yeslia Utubira; Jaya Tuahuns (Molluca Journal of Chemistry Education (MJoCE), 2011)
A research has conducted to know student’s study result after the application of the student’s work paper base contextual of material on solubility and solubility multiplication result. This type of this research was descriptive to describes the symptoms accurred in it by using XI IPA class of SMA Negeri 4 Leihitu as research subject. The data was taken from student’s study result, cognitive tests per meeting. From the data collected, it might be concluded that the application of student’s work paper experiments based contextual might motivate the student’s activitites in teaching learning process and improve their study result with minimal completeness standard 80.36%